Quantitative Comparison of Pyranose Dehydrogenase Action on Diverse Xylooligosaccharides - Karppi, Johanna; Zhao, Hongbo; Chong, Sun-Li; Koistinen, Antti E.; Tenkanen, Maija; Master, Emma (Frontiers in Chemistry, 2020)
Pyranose dehydrogenases (PDHs; EC 1.1.99.29; AA3_2) demonstrate ability to oxidize diverse carbohydrates. Previous studies of these enzymes have also uncovered substrate-dependent regioselectivity, along with potential to introduce more than one carbonyl into carbohydrate substrates. Enzymatic oxidation of carbohydrates facilitates their further derivatization or polymerization into bio-based chemicals and materials with higher value; accordingly, PDHs that show activity on xylooligosaccharides could offer a viable approach to extract higher value from hemicelluloses that are typically fragmented during biomass processing. In this study, AbPDH1 from Agaricus bisporus and AmPDH1 Leucoagaricus meleagris were tested using linear xylooligosaccharides, along with xylooligosaccharides substituted with either arabinofuranosyl or 4-O-(methyl)glucopyranosyluronic acid residues with degree of polymerization of two to five. Reaction products were characterized by HPAEC-PAD to follow substrate depletion, UPLC-MS-ELSD to quantify the multiple oxidation products, and ESI-MSn to reveal oxidized positions. A versatile method based on product reduction using sodium borodeuteride, and applicable to carbohydrate oxidoreductases in general, was established to facilitate the identification and quantification of oxidized products. AbPDH1 activity towards the tested xylooligosaccharides was generally higher than that measured for AmPDH1. In both cases, activity values decreased with increasing length of the xylooligosaccharide and when using acidic rather than neutral substrates; however, AbPDH1 fully oxidized all linear xylooligosaccharides, and 60-100% of all substituted xylooligosaccharides, after 24 h under the tested reaction conditions. Oxidation of linear xylooligosaccharides mostly led to double oxidized products, whereas single oxidized products dominated in reactions containing substituted xylooligosaccharides. Notably, oxidation of specific secondary hydroxyls versus the reducing end C-1 depended on both the enzyme and the substrate. For all substrates, however, oxidation by both AbPDH1 and AmPDH1 was clearly restricted to the reducing and non-reducing xylopyranosyl residues, where increasing the length of the xylooligosaccharide did not lead to detectable oxidation of internal xylopyranosyl substituents. This detailed analysis of AbPDH1 and AmPDH1 action on diverse xylooligosaccharides reveals an opportunity to synthesize bifunctional molecules directly from hemicellulose fragments, and to enrich for specific products through appropriate PDH selection.